Analisis Kualitas Website Tribunnews.com Menggunakan Metode Webqual dan Importance Performance Analysis - Ernesto Ersada Barus; Suprapto Suprapto; Admaja Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The development of technology today is directly proportional to the rapid growth of online information media. The growth of online media is getting attention from internet users in Indonesia whose numbers also increased sharply. Media companies are starting to glance at this market. Media companies are beginning to provide online media such as creating websites. Tribunnews, Detik, Liputan6, Kompas are a handful of examples of online media most frequently accessed by internet users. Tribunnews became the most frequently accessed online medium based on data from Alexa. Therefore, the purpose of this study would like to discuss the extent to which the quality of tribunnews.com website based on user perceptions. Therefore, this research uses webqual method that focuses on usability, information quality, and service interaction quality based on voice of customer (user perception). The IPA method is useful in analyzing the degree of conformity based on user perceptions with user expectations. This IPA method will also be able to show the level of gap between user perceptions and user expectations which are further illustrated in the IPA quadrant. This research instrument uses questionnaires. The population of this study is the general public who have accessed the website tribunnews.com with random sampling technique. The results of this study can be a reference for the development of the website tribunnews.com and can add a library of webqual and IPA methods.